Electrochemical Bromination of Acetanilide in Protic Media at Graphite and Platinum Anodes - ABIRAMI, D.; CHITHRA, B.; KRISHANAMOORTHY, T.K. (Asian Journal of Chemistry, 2010)
Electrochemical bromination of acetanilide with sodium bromide in 5 % acetic acid solution at graphite/platinum anode has been carried out. o- and p-Bromoacetanilides are the products on platinum where as p-bromoacetanilide and a benzidene derivative have been isolated at graphite and their identities confirmed by chromatographic and PMR spectral studies. While conventional aromatic electrophilic substitution with bromonium ion has been conceived at platinum electrode, a nucleophilic attack by bromide ion on a cation radical is the obvious choice at the graphite electrode.